The managerial conversion of senior civil servants: a convenient myth for the French local welfare state? - Alcaras, Jean-Robert et al (2016)
Has New Public Management really been rolled out homogenously across the board? Drawing on research into the viewpoints and practices of a particular category of senior civil servants in France (those in charge of local welfare policy), this article takes a critical look at this assumption of convergence towards NPM. Behind a discursive convergence that remains superficial and partial, the reality tends more towards heterogeneous and contextualized appropriations of New Public Management benchmarks often leading to new forms of bureaucracy. In a context where the position of public officials has been weakened, management seems to have been adopted as a source of professional legitimization. By adopting this very useful managerial posture, these civil servants find comfort in perpetuating the myth of convergence. - Reproduced.
Keywords: Public administration; Civil service